2013
DOI: 10.3390/ijerph10083735
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Australian Mosquito Species in the Transmission of Endemic and Exotic West Nile Virus Strains

Abstract: Recent epidemic activity and its introduction into the Western Hemisphere have drawn attention to West Nile virus (WNV) as an international public health problem. Of particular concern has been the ability for the virus to cause outbreaks of disease in highly populated urban centers. Incrimination of Australian mosquito species is an essential component in determining the receptivity of Australia to the introduction and/or establishment of an exotic strain of WNV and can guide potential management strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 103 publications
(151 reference statements)
0
15
0
Order By: Relevance
“…Although the amount of virus required for transfusion transmission is not known, this suggests that high levels of viremia may be required to transmit virus by transfusion, a probability that may be further reduced with even modest reduction in infectious titer of these agents. Moreover, PRT has the added potential benefits of negating the need for implementing new screening tests in particular areas, where a suitable test may exist but is either not yet available or not yet in use, such as malaria screening in the United States or Canada or WNV testing in Australia, as well as eliminating the need for certain travel‐related donation deferrals, which may have a flow on effect of addressing accessibility issues. Studies have also demonstrated that PRT appears to be as cost‐effective as other blood safety methods .…”
Section: Discussionmentioning
confidence: 99%
“…Although the amount of virus required for transfusion transmission is not known, this suggests that high levels of viremia may be required to transmit virus by transfusion, a probability that may be further reduced with even modest reduction in infectious titer of these agents. Moreover, PRT has the added potential benefits of negating the need for implementing new screening tests in particular areas, where a suitable test may exist but is either not yet available or not yet in use, such as malaria screening in the United States or Canada or WNV testing in Australia, as well as eliminating the need for certain travel‐related donation deferrals, which may have a flow on effect of addressing accessibility issues. Studies have also demonstrated that PRT appears to be as cost‐effective as other blood safety methods .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of WNV in most of the United States already a decade ago and its spread to all regions of the continental US throughout this decade [13] , WNV epidemic activity was demonstrated in 2012, in which more human disease cases were reported nationally than any year since 2003. This outbreak resulted in 2,873 cases of neuroinvasive disease and 286 human deaths [14] , [15] . Available data suggest that the increased incidence of WNV disease in 2012 was not likely caused by genotypic changes in the circulating virus strains and it was suggested that a number of inter-related factors, including weather, abundance of birds that maintain the virus, abundance of mosquitoes that spread the virus, and human behaviour are all contributors to the disease epidemics [16] .…”
Section: Introductionmentioning
confidence: 99%
“…The season of arbovirus activity might be prolonged, with potential transmission increase [101]. Moreover, as a result of temperature increase, the vectors are expected to move further south into currently cooler regions because summer temperatures in southern areas will be more adequate for initiating and maintaining the virus amplification [102,103].…”
Section: (B) Climate Change Impact On West Nile Virus Transmissionmentioning
confidence: 99%